PENGARUH INFLASI DAN PRODUK DOMESTIK BRUTO (PDB) TERHADAP JUMLAH UANG BEREDAR DI INDONESIA TAHUN 1987-2017 (PENDEKATAN ARDL) - Sabbahatul Khairiati; Cut Putri Mellita Sari (LPPM UNIMAL, 2019)
The study aims to determine the effect of inflation and gross domestic product (GDP) on the Amount of Money Supply (JUB) in Indonesia. The data used in the study are time-series data from 1987 to 2017 obtained from the Central Bureau of Statistics, Ministry of Trade, and Bank Indonesia. The method of data analysis uses the ARDL (Auto-Regressive Distributed Lagged) approach. The results showal that all variables are stationary at the first difference and are co-integrated in the long run. The model stability test results showal that the model used partially stable in the short-term, inflation had a positive and significant effect on the Amount of Money Supply in Indonesia and the Gross Domestic Product had a positive and significant effect on the Money Supply in Indonesia. In the long run showad that inflation ad negative and insignificant effect on economic growth in Indonesia, had Gross Domestic Product hade a positive and insignificant effect on the Amount of Money Supply in Indonesia.